Perceptibility and Experience of Inner-European Borders by Institutionalised Border Protection - Pudlat, Andreas (Quaestiones Geographicae, 2010)
The article concentrates on institutionalised border protection as a special indication of border areas that are demarcated by the existence and operations of specific authorities. This kind of border protection with its control and monitoring measures serves different purposes, including crime fighting and protection against threats, fiscal aspects (customs), migration control, traffic safety, and environment protection. Furthermore, it is an expression of state sovereignty. In this way borders and border areas can be experienced and perceived, which the article suggests can have different dimensions: a cognitive, an affective, a visual-haptic, and an aesthetic one. Under the Schengen Agreement, systematic border control between the participating states has been removed. This implies, not the end of border protection, but perhaps a loss of a manifestation and perceptibility of borders and border areas.